Strategic Marketing Management for Enhancing Educational Quality: A Case Study of TK Perjuangan in Babakan Village - Maula, Nichlatul; Rifai, Ahmad; Sa’adah, Vina Iqomatus (Transformation of Islamic Management and Education, 2024)
This study aims to analyze the implementation of marketing management in improving the quality of education at TK Perjuangan, located in Babakan Village, Ciwaringin District, Cirebon Regency. Using a descriptive qualitative approach, the study collects data through in-depth interviews with the school principal, teachers, and parents, as well as official documents such as activity reports and promotional materials. The results indicate that TK Perjuangan has successfully implemented a marketing strategy that covers product, price, and promotion aspects. The product strategy focuses on the flagship program, which is the Iqro learning method, while the price strategy offers flexible payment options for parents. Promotion is carried out through social media and print media to reach a broader audience. Supporting factors identified include the competence of educators and support from the foundation's leadership, while challenges faced include intense competition and variations in students' abilities. The implications of this study suggest that effective marketing management not only enhances the institution's appeal but also contributes to the improvement of educational service quality. These findings can serve as a reference for other educational institutions in formulating relevant marketing strategies to enhance their educational quality.